Influence of heart failure severity on heart rate variability - Zamaklar-Trifunović Danijela (Srpski Arhiv za Celokupno Lekarstvo, 2005)
Introduction. Autonomic regulation of cardiovascular functions in congestive heart failure is characterised by enhanced sympathetic and diminished parasympathetic activity. The long term predominance of sympathetic tone is a significant factor in arrhythmogenesis, sudden cardiac death, and progressive pump failure. Heart rate variability (HRV) is a noninvasive method for estimating the sympatho vagal balance in cardiovascular control. Aim. The aim of this study was to analyse the influence of heart failure severity on HRV. Method. HRV was estimated through the spectral analysis of short term ECG (Cardiovit AT 60, Schiller, CH) in 63 patients (78% male, mean age 56.9±10.9 years) and 14 healthy volunteers (57.1% male, mean age 53.1±8.2 years). The following spectral components were measured: VLF (very low frequency), LF (low frequency), HF (high frequency), and total power (Tot Power). Results. All spectral components were statistically, significantly lower in patients with heart failure in comparison to healthy controls (VLF: 159.89±147.02 vs. 285.50±202.77 ms2; p=0.023, LF: 161.48±204.01 vs. 474.57±362.93 ms2; p<0.001, HF: 88.58±102.47 vs. 362.71±318.28 ms2; p<0.001), as well as total power (Tot Power: 723.39±644.52 vs. 1807.29±1204.74 ms2; p<0.001). A significant, negative correlation between HRV parameters and NYHA class was detected in heart failure patients (VLF: r=-0.391; p=0.002, LF: r=-0.401; p=0.001, and Tot Power r=-0.372; p=0.003). Ejection fraction proved to be in significant, positive correlation to VLF (r=0.541; p=0.002), LF (r=0.531; p=0.003), HF (r=0.418; p=0.020), and Tot Power (r=0.457; p=0.013). Conclusion. Significant HRV reduction is a precursor to incipient heart failure (NYHA I). In heart failure progression, total power as well as the power of all spectral components is progressively reduced. LF and Tot Power are the most prominent parameters for discriminating between the different stages of heart failure. These results could promote HRV as an important decision-making tool in heart failure treatment as well as in monitoring the results of that treatment.